(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
This study seeks to confirm the relationship that exists between Production Improvement Function (PIF) Quality of Service (QOS), and Quality of Delivery (QOD), in Nigerian refineries. One hundred and twenty-four respondents from four refineries constituted the sample size, and data was collected through research questionnaires through a research questionnaire. The data was analyzed using structural equation modeling (SEM). The results show that there is a high positive correlation between production improvement functionality and both quality of service (β = 0.724, p = 0.000) and quality of deliveries (β = 0.652, p = 0.000). Nevertheless, more research into the causal channels that resolve into continuous refinement of service quality needs to be performed. Recommended strategies for implementation and further development include collectivized progress schemes, investment in the latest technology, systematic employee training, and effective chain management. Applying these recommendations is very important (fighting for) operational efficiency, service quality, and customer satisfaction in Nigerian refineries in the long term with long-term success and competitiveness in the market